Compressive strength of premolars restored with ceramic crowns and supported with a glass fiber post using different luting agents - Flávia Carvalho de Oliveira Paixão; Vandilson Pinheiro Rodrigues; Roy George; Soraia de Fátima Carvalho Souza; Antonio Ernandes Macêdo Paiva; Adriana de Fátima Vasconcelos Pereira (Elsevier, 2022)
Objective: The retention of glass fiber post (GFP) is considered a key factor for the long-term success of restorations of endodontically treated teeth. This study aimed to compare the compressive strength of a ceramic crown supported by a GFP using different luting agents. Methods: Forty single-rooted premolars were randomly divided into four groups (n = 10 each): control group (teeth without a GFP), Ketac Cem group (glass ionomer), RelyX ARC group (conventional dual-curing resin), and RelyX U200 group (self-adhesive dual-curing resin). After luting of the posts and placement of all-ceramic crowns made using feldspathic porcelain (Noritake EX-3), they were exposed to thermocycling for 1000 cycles and compressive strength tests. Statistical analysis included Kruskal-Wallis test with Dunn's multi-comparison test. Results: The Ketac Cem group and RelyX U200 group showed significantly greater fracture resistance to compressive loading than the control group. Conclusion: This study indicates a possible role of the luting agent used with the GFP in influencing the compressive strength of the restored teeth. In this study, the self-adhesive dual-curing resin and glass ionomer both offered resistance to fractures.